Baguio address no.10. - Aquino, Mervine Anjelo Veneracion (2018)
"Baguio Address No. 10 is an experimental film revolving primarily around the filmmaker's family's experiences of constantly having to move from one house to another. The work connects past home videos, old photographs, recorded conversations, and mobile phone videos in an attempt to dream of a future home through cinema. The work is an inquiry into video media and how it serves as a vessel of remembering and forgetting. Studies on video practices by Sean Cubitt and Marita Sturken primarily guide the work. By documenting the present through an outdated medium, Hi-8, it addresses the materiality of video media, to which we attach our nostalgia. Furthermore, it seeks to move personal history, memory and dreams forward through the digital form."